Boccaccio's Demogorgon and Renaissance Platonism. (2nd January 2019) - Coleman, James K.
ABSTRACT: The shadowy deity Demogorgon, whom Giovanni Boccaccio identifies as the uncreated progenitor of the pagan pantheon, enjoyed an illustrious literary afterlife. The information about Demogorgon that Boccaccio presents in the Genealogie deorum gentilium libri [ Genealogy of the Pagan Gods ] (and which Boccaccio claims derives indirectly from a lost, extremely ancient Greek poem) captured the interest of thinkers connected with the fifteenth- and sixteenth-century revival of Platonism and syncretism, as this essay will demonstrate by examining Demogorgon's presence in the works of three Renaissance authors: Ugolino Verino, Marsilio Ficino, and Leone Ebreo.